The Toxicity Potential of Antidepressants and Antipsychotics in Relation to Other Medication and Alcohol: A Naturalistic and Retrospective Study - Swoboda, Marleen M. M.; Bartova, Lucie; Dremel, Marlene; Rabl, Ulrich; Laggner, Anton; Frey, Richard (Frontiers in Psychiatry, 2022)
QT interval prolongation and ventricular tachyarrhythmia are potential adverse effects of antidepressant (AD) and antipsychotic- (AP) agents, especially when overdosed. Since AD and AP agents are often prescribed to patients suffering from suicidal intentions, it is essential to estimate these risks in the context of intoxications. This retrospective and naturalistic one-year registry study included 105 patients treated for oral intoxication at the University Department of Emergency Medicine in Vienna, Austria. AD/AP intoxications were present in 26 patients, while in the control group (n = 79) non-AD/AP drugs (n = 54) and alcohol (n = 25) where the main toxic agents. QT intervals, the necessity of intubation, the extent of conscious state, and the subsequent discharge management were compared. The mean age was 34.94±14.6 years, 62 patients (59%) were female. There were no significant between-group differences regarding QT prolongation > 470 ms using Bazett’s correction (p = .178), or > 440 ms using Fridericia’s correction (p = .760). No significant group differences concerning the need for intubation were observed (p = .747). The AD/AP and the control group did not significantly differ regarding Glasgow Coma Scale scores (p = .439). Patients with AD/AP intoxication were significantly more often transferred to the psychiatric department, while discharge to home was more likely in the control group (p = .002). These results suggest that the risk of a potentially life-threatening outcome in cases of intoxication with AD/AP is not substantially higher than in other easily available toxic agents, in line with the advantageous risk/benefit ratio of newer ADs and APs.